Decreased plasma in basal cell cancer (Bangladesh Journal of Medical Science, 2024)
Aim Basal cell carcinoma (BCC) is one of the most common malignant non-melanoma carcinomas and is an important health problem for all countries. There are many studies on the effect of human lipoprotein metabolism and high-density lipoprotein (HDL-C) function on skin cells, but there are no detailed clinical studies on BCC yet. In addition, higher phospholipid and cholesterol content was found in cancerous and precancerous lesions of the skin compared to normal tissue. The aim of our study was to evaluate the lipid profile in patients with BCC and to try to find any relationship between BCC and molecules that have an important place in HDL-C functionality. Methods The patient group consisted of 39 patients who were clinically diagnosed with BCC by biopsy in hospital clinics. The control group (n:44) was randomly selected from patients of the same age group without a diagnosis of BCC who applied to different clinics of the same hospital. Routine lipid level, Apolipoprotein A1 (Apo-A1) level and Paraoxonase (PON- 1) enzyme measurements were made from serum samples taken from the patients and control groups participating in the study. Results The most important findings of this study, a statistically significant decrease in serum Apo-A1 level and a decrease trend in PON-1 enzyme can be considered in BCC patients compared to control groups. Conclusion Lipid metabolism and HDL functionality, may play a role in the development of BCC.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1060-1067